Innovation in Developing and Teaching the Management of Micro-mobility - Judita Peterlin; Marko Grguric; Mateja Dovjak (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
Our paper presents teaching, learning, management, and recommendations for promoting the safe usage of micro vehicles, a trend in today's traffic. However, since we do not know how to use new vehicles in our traffic, the trend of incidents, severe injuries, and even first deaths is quickly rising. Therefore, we are developing tools and good practice examples for promoting the safe usage of micro vehicles, such as e-scooters and e-bikes. We also provide results of our empirical study based on the Stanford Social Innovation Questionnaire, researching common mistakes when using micro vehicles and ways to help promote the safe usage of e-scooters. In conclusion, we provide recommendations for further research. We firmly believe that our educational and teaching change, fostered by innovations in learning, teaching process, and technology for learning, teaching, and curriculum development, can serve as a model for other countries grappling with the challenges of micro-mobility, thereby contributing to the global discourse on traffic safety.
Keywords: H75; M00; 330; micro-mobility; experiential learning; social innovation; action research; management